Pay satisfaction among doctors and nurses in a tertiary hospital in South-South Nigeria - Ozumba, Lillian N.; Alabere, Ibidabo D. (International Journal of Research in Medical Sciences, 2021)
Background: Employee pay is an important area in human resources management which influences individual behaviour including absenteeism in organizations. Pay satisfaction is a primary concern to employees because of its importance in satisfying their economic needs. The research was conducted to determine the occurrence and factors affecting employee pay satisfaction among doctors and nurses working in a tertiary hospital. Methods: A descriptive, cross-sectional study design was used for this research on a sample of 320 doctors and nurses in a tertiary hospital that were selected using stratified sampling technique. An interviewer-administered questionnaire containing pay satisfaction details amongst others was used to collect data from the respondents. The data was analysed using statistical package for social sciences version 22 and statistical significance was set at 0.05. The results were presented in tables. Results: The prevalence of pay satisfaction in this study was 16.9%. Specifically, monthly earning (p=0.003) and job category (p=0.008) were found to be significantly associated with pay satisfaction. Conclusions: This study showed that the prevalence of respondents that were satisfied with their pay was low. There is need to apply practical measures that will improve pay satisfaction among doctors and nurses so as to improve productivity in the health sector.